Perceived Stress and Life Satisfaction Among Chinese Clinical Nursing Teachers: A Moderated Mediation Model of Burnout and Emotion Regulation - Xu, Xia; Chen, Ling; Yuan, Yuan; Xu, Ming; Tian, Xiaocui; Lu, Fang; Wang, Zonghua (Frontiers in Psychiatry, 2021)
Our previous study indicated that clinical teaching nurses in China suffered high levels of perceived stress and burnout, mainly because they were taking double responsibilities of nursing and teaching at the same time. The study aimed to investigate the underlying mechanisms of how and when perceived stress increased the risk of burnout and decreased life satisfaction among clinical teaching nurses. Questionnaires about perceived stress, burnout, emotion regulation and life satisfaction were self-administered to 1372 teaching nurses from eight tertiary military hospitals in China. Correlation and hierarchical multiple regressions were employed for data analysis. The results revealed that perceived stress had direct and indirect impacts on life satisfaction, with the principal element of burnout- emotional exhaustion acting as a mediator. Moreover, the association between perceived stress and emotional exhaustion was moderated by emotion suppression- a key emotion regulation strategy. The negative impact of perceived stress on burnout was stronger among teaching nurses with high emotion suppression than among those with low emotion suppression. The present study contributed to a deeper understanding of the relationship between perceived stress and life satisfaction; and also suggested further research into emotion regulation interventions to alleviate or eliminate the impact of perceived stress on burnout, and eventually improve the life satisfaction for Chinese clinical nursing teachers.